Saving Behavior Determinants in Malaysia: An Empirical Investigation - Ismail, Shafinar; Koe, Wei-Loon; Halim Mahphoth, Mohd; Abu Karim, Rizuwan; Yusof, Noorhidayah; Ismail, Suzila (KnE Social Sciences, 2020)
This study investigates the determinants of saving behavior among government servants. The study focused on financial knowledge, financial self-efficacy, financial attitude and financial management practice in relation of saving behavior. The respondents were government servants in Kuala Lumpur, Malaysia. Convenience sampling was used for this study. 150 questionnaires were distributed to 150 respondents to answer the questionnaires. The questionnaire was designed in two sections, one consisting of demographic information and the second relating to the selection determinants of saving behavior. Result indicates that financial self-efficacy becomes an important factor that influences the saving behavior. Financial self- efficacy is the best predictor as most of government servants are managed to make progress towards financial goals. These findings could be useful references for related organizations as well as body of knowledge and practical implication that are interested in developing personal saving in a context of avoiding from bankruptcy. Keywords: Saving Behavior, Financial Knowledge, Financial Attitude, Financial Self- Efficacy, Financial Management Practice